2011
DOI: 10.1007/s00127-011-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and social support as predictors and mediators of eating disorder carer burden and psychological distress

Abstract: Interventions focusing on teaching appropriate coping strategies would benefit carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 43 publications
3
54
2
5
Order By: Relevance
“…Results of the regression analysis revealed maladaptive coping styles to be a significant predictor of increased psychological distress, which is in agreement with the findings of other published studies (Coomber & King ; Kartalova‐O'Doherty & Doherty ; Mackay & Pakenham ). Mackay and Pakenham () found that IC ( n = 87) of individuals with non‐specific mental illnesses, who relied on predominantly maladaptive coping styles, had poorer general health and experienced greater psychological distress.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results of the regression analysis revealed maladaptive coping styles to be a significant predictor of increased psychological distress, which is in agreement with the findings of other published studies (Coomber & King ; Kartalova‐O'Doherty & Doherty ; Mackay & Pakenham ). Mackay and Pakenham () found that IC ( n = 87) of individuals with non‐specific mental illnesses, who relied on predominantly maladaptive coping styles, had poorer general health and experienced greater psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…Many IC report insufficient support and are unsure of how to obtain more (Douma et al . ), with lower levels being associated with maladaptive coping styles (Coomber & King ) and high levels of psychological distress (Wijndaele et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as in the sample in Hibbs, Rhind, et al (), the percentage of mothers who were the primary caregiver was notably higher than that of fathers. Previous studies on caregivers and ED patients have reported a larger number of mothers take on this role compared with fathers (Coomber & King, ; Graap et al, ; Jauregui‐Lobera, Ruiz‐Prieto, Bolanos‐Rios, & Garrido‐Casals, ; Macdonald et al, ; Martín et al, ). These results are in line with the current literature highlighting the predominance of female caregivers across mental disorders (Graap et al, ; Roick, Heider, Toumi, & Angermeyer, ; Souza et al, ; Stadnick, Chlebowski, & Brookman‐Frazee, ).…”
Section: Discussionmentioning
confidence: 98%
“…Although no previous studies have explored this issue in families of children with obesity, several studies have assessed the use of coping strategies among caregivers of patients with EDs. These studies have revealed that caregivers' use of maladaptive coping strategies were associated with psychological distress (Coomber & King, ) and that mothers tend to use similar coping strategies as their adolescent daughters with an ED (Lantzouni, Cox, Salvator, & Crosby, ). Future studies are needed to assess if these same findings hold true for those caring for offspring with obesity.…”
Section: Discussionmentioning
confidence: 99%